The sound of cooperation : musical influences on cooperative behavior - Kniffin, Kevin M. (2020)
Music as an environmental aspect of professional workplaces has been closely studied with respect toconsumer behavior while sparse attention has been given to its relevance for employee behavior. In this arti-cle, we focus on the inﬂuence of music upon cooperative behavior within decision-making groups. Based onresults from two extended 20-round public goods experiments, we ﬁnd that happy music signiﬁcantly andpositively inﬂuences cooperative behavior. We also ﬁnd a signiﬁcant positive association between moodand cooperative behavior. Consequently, while our studies provide partial support for the relevance of affectin relation to cooperation within groups, we also show an independently important function of happy musicthat ﬁts with a theory of synchronous and rhythmic activity as a social lubricant. More generally, our ﬁndingsindicate that music and perhaps other atmospheric variables that are designed to prime consumer behaviormight have comparably important effects for employees and consequently warrant closer investigation.